The Effect of Product Quality, WOM (Word Of Mouth), Price on Interest to Buy at Nyamleng Rice Stop in Village - Annafik Asmaul Khusna; Misti Hariasih (Indonesian Journal of Cultural and Community Development, 2023)
This study aims to determine the effect of Product Quality, WOM, and Price on Interest in Buying Warung Nasi Pecel Nyamleng. This research is descriptive research using quantitative methods. The population used in this study were visitors who had bought at Warung Nasi Pecel Nyamleng, totaling 96 respondents using the accidental sampling technique. This study uses data collection techniques used as a questionnaire. The data analysis technique used in this research is Multiple Linear Regression analysis using SPSS version 25 for Windows. The results of this study indicate that product quality has a significant effect on buying interest, the promotion has a significant effect on purchase interest, and the price has a significant impact on buying interest.